Indicators of Conservation Value of Azorean Caves Based on its Bryophyte Flora at Cave Entrances - Gabriel, Rosalina (2008)
Cave entrances in the Azores are particularly humid habitats. These provide opportunities for the colonization of a diverse assemblage of bryophyte species. Using both published data and new field sampling, we evaluated species diversity and rarity of bryophytes at the entrance of all known Azorean lava tubes and volcanic pits with such flora. Frequent species include the liverworts: Calypogeia arguta, Jubula hutchinsiae or Lejeunea lamacerina, and the mosses: Epipterygium tozeri, Eurhynchium praelongum, Fissidens serrulatus, Isopterygium elegans, Lepidopilum virens and Tetrastichium fontanum. Several rare Azorean bryophyte species appear at some cave entrances (e.g. Archidium alternifolium; Asterella africana; Plagiochila longispina), which reinforces the importance of this habitat for the regional conservation of these plants. To produce an unbiased multiple-criteria index (Importance Value for Conservation, IV-C), several indices based on bryophyte diversity and rarity, and also geological and management features, were calculated for each cave, and an iterative partial multiple regression analyses was performed. Data sows that three pit caves are particularly diverse in bryophytes (Algar do Carvão, Terceira Island, Bocas do Fogo, S. Jorge and Furna do Enxofre, Graciosa). Lava tubes with a diverse troglobitic fauna also are diverse in terms of bryophyte species (e.g., Algar do Carvão, Gruta dos Montanheiros, Gruta da Agostinha, Furna do Henrique Maciel). We also evaluate the utility of several cave management indices as surrogates of bryophyte diversity in Azorean volcanic cavities.